1995
DOI: 10.1142/s0217732395001393
|View full text |Cite
|
Sign up to set email alerts
|

Tachyon Effects on the Two-Dimensional Black Hole Geometry

Abstract: We study solutions of the tree level string effective action in the presence of the tachyon mode.We find that the 2-dim. static black hole is stable against tachyonic perturbations.For a particular ansatz for the tachyon field we find an exact solution of the equations of motion which exhibits a naked singularity.In the case of static fields we find numerically that the full system has a black hole solution,with the tachyon regular at the horizon.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 9 publications
2
19
0
Order By: Relevance
“…As another non-trivial application of the Liouville approach to time, we consider the dilaton-matter black-hole solution found in [37]. In two dimensions, the action of the dilaton-tachyon system coupled to gravity is…”
Section: The Arrow Of Liouville Time In Two-dimensional String Universesmentioning
confidence: 99%
See 1 more Smart Citation
“…As another non-trivial application of the Liouville approach to time, we consider the dilaton-matter black-hole solution found in [37]. In two dimensions, the action of the dilaton-tachyon system coupled to gravity is…”
Section: The Arrow Of Liouville Time In Two-dimensional String Universesmentioning
confidence: 99%
“…One solution of the equations of motion derived from this action is the static black hole of [36], which from a string theory point of view is an equilibrium (conformal) fixed point solution in the space of string theories. A non-equlibrium exact solution appears [37] when one considers collapsing tachyonic (massless) matter, T = T (x + ), where x + is a light-cone coordinate. The solution is characterised by an initial singularity at x + = 0 and the absence of a white hole.…”
Section: The Arrow Of Liouville Time In Two-dimensional String Universesmentioning
confidence: 99%
“…For general λ 2 = 0, i.e., central charges c = 26, as seen in (2), the above solution has the structure of a non-static time-dependent black hole, with the important feature [5] that there is a tachyon singularity at x + = 0, which is displayed in Fig. 1.…”
Section: Review Of the Two-dimensional Dilaton Blackmentioning
confidence: 94%
“…For completeness, we first review relevant aspects of the dilaton-matter black-hole solution found in [5]. In two dimensions, the action of the dilaton-tachyon system coupled to gravity is…”
Section: Review Of the Two-dimensional Dilaton Blackmentioning
confidence: 99%
See 1 more Smart Citation